Christianity, philosophy, and Roman power : Constantine, Julian, and the bishops on exegesis and empire - Niccolai, Lea, 1991- (Greek culture in the Roman world, 2023)
This book rethinks the Christianisation of the late Roman empire as a crisis of knowledge, pointing to competitive cultural re-assessment as a major driving force in the making of the Constantinian and post-Constantinian state. Emperor Julian's writings are re-assessed as key to accessing the rise and consolidation of a Christian politics of interpretation that relied on exegesis as a self-legitimising device to secure control over Roman history via claims to Christianity's control of paideia. This reconstruction infuses Julian's reaction with contextual significance. His literary and political project emerges as a response to contemporary reconfigurations of Christian hermeneutics as controlling the meaning of Rome's culture and history. At the same time, understanding Julian as a participant in a larger debate re-qualifies all fourth-century political and episcopal discourse as a long knock-on effect reacting to the imperial mobilisation of Christian debates over the link between power and culture.